STRATEGI ASEAN MENGHADAPI PERSAINGAN KEKUATAN AMERIKA SERIKAT DAN CHINA DI KAWASAN INDO-PASIFIK - Syahroni Albi; Umi Oktyari Retnaningsih; Yusnarida Eka Nizmi (Journal Publicuho, 2021)
ASEAN is an international organization in Southeast Asia that holds up the principle non-interference and non-alignment, but this principle cannot be maintained in the face of the power competition that occurs between the United States and China in the Indo-Pacific Region. The ten ASEAN member countries have different national interests. Some ASEAN member countries support the United States while some others support China. Having different national interests causes ASEAN member countries to have different views on the power competition that occurs between the United States and China. ASEAN has an interest in safeguarding its region so that's it remains in a stable, safe, and prosperous condition. So that prevents the division of unity among these member countries, ASEAN must have a strategy to maintain regional stability. The theory used in this research is Clive Archer's theory of international organization and the theory of interdependence from Keohane and Joseph S. Nye. The research method used is qualitative, and the data collection technique used in this research is  a literature study. The results of this study indicate that ASEAN uses the ASEAN Outlook on the Indo-Pacific (AOIP) strategy which was agreed upon by all member countries at the 34th ASEAN Summit in Bangkok. ASEAN does not take side with one of the major power countries but to the prioritize cooperation in the fields of maritime, connectivity, SDGs, and the economy.